Identifikasi Kadar Hemoglobin Rendah pada Calon Pendonor Darah di Yogyakarta: Identification of Low Hemoglobin Levels in Prospective Blood Donors in Yogyakarta - Arif Tirtana; Lusia Peni Lamen; Wiwit Sepvianti; Aulia Rahman; Gravinda Widyaswara; Kumara Rahmawati Zain; Selasih Putri Isnawati Hadi (Journal of Health, 2025)
Hemoglobin (Hb) is influenced by several factors, including unhealthy lifestyle, age, gender, food and drink. Hb binds and carries oxygen from the lungs to be distributed to all body tissues. Hb deficiency can cause anemia which can cause morbidity and mortality for sufferers. This research is to determine the risk factors for low hemoglobin levels in potential donors. This research method is descriptive observational. The sample was 50 blood donor respondents who did not pass the selection with Hb levels ≤ 12.5 g/dL. The results of research regarding the description of risk factors for low hemoglobin levels in blood donors at UTD PMI Yogyakarta City showed that donors with low hemoglobin levels were mostly 25 (50.0%) aged 17-25 years, 25 (50%) had the habit of drinking tea twice a day. .0%), drink coffee twice a day as many as 23 (46.0%), rarely consume vegetables as many as 29 (58.0%), consume fruit twice a week as many as 35 (70.0%), smokers moderate (11-20 cigarettes/day) as many as 38 people (76%) and the habit of staying up late 3 times a week as many as 25 (50.0%). In conclusion, low Hb levels in potential donors aged 17-25 years are caused by the habit of drinking tea, the habit of drinking coffee, rarely consuming vegetables, rarely consuming fruit, moderate smoking and the habit of staying up late.